Small pleasures: adaptation and the past in British film and television - John Caughie (Ilha do Desterro)
The adaptation of classic literature, or more precisely the construction of certain literary works as classic—the classic serial—has een a characteristic of British television almost since television began. Certainly, since television resumed its normal service after the break in transmission enforced by World War II, the novels of Jane Austen, the Brontë sisters, Conrad, Dickens, and occasionally Henry James, have been adapted and sometimes readapted. In the mid-1990s, adaptations of Pride and Prejudice (1995), Middlemarch (1994) and Martin Chuzzlewit (1994) not only reaffirmed the status of the BBC as the cornerstone of national broadcasting, but also confirmed its cultural prestige overseas. It also, of course, secured it a healthy slice of the substantial international market in 'quality television’. In the 1980s, endless adaptations of E.M.Foster, suffused with the charms of manners and costume and basking in the warm glow of the past, have made adaptation a cultural dominant in representations of Britain, helping to shape the perception of Britishness - or at least of Englishness - as a quality whose real meaning can be found in the past, and whose commodity value can be found in the heritage industry. Revealingly, the Government Ministry now charged with the administration of culture in Britain has been renamed the Department of National Heritage.